Compliance of the ‘Batas Kasambahay’ (Ra 10361) Among Domestic Employers in Zamboanga Del Norte: Basis for Bureaucratic Intervention - Mansanadez, Evangeline; Lapinig, Ruthie Liza (JPAIR Multidisciplinary Research, 2019)
Every human being has its own rights and privileges to be enjoyed for a lifetime. To have a happy and secure means of living is always a dream of every individual. This study is designed to determine the compliance of the “Batas Kasambahay” (RA 10361) among domestic employers in Zamboanga del Norte as the basis for bureaucratic intervention. It utilized descriptive normative survey method of research employing the questionnaire as the main data gathering tool; employing frequency count, simple percentage, and Likert’s method of determining the weighted mean; utilizing the 30 kasambahay working in households situated in the Poblacion areas of the towns in the three Congressional Districts within the territorial jurisdiction of the province of Zamboanga del Norte. Findings led to the conclusion that the mandated right to board and lodging and medical attendance, humane treatment, and access to communication were compiled by the majority of the domestic employers. However, their rights for social and other benefits and incentives were not complied with by the latter.